Uncovering Inherited Cardiomyopathy With Human Induced Pluripotent Stem Cells - Jiang, Xue; Chen, Yihuan; Liu, Xiaofeng; Ye, Lingqun; Yu, Miao; Shen, Zhenya; Lei, Wei; Hu, Shijun (Frontiers in Cell and Developmental Biology, 2021)
In the past decades, researchers discovered the contribution of genetic defects to the pathogenesis of primary cardiomyopathy and tried to explain the pathogenesis of these diseases by establishing a variety of disease models. Although human heart tissues and primary cardiomyocytes have advantages in modeling human heart diseases, they are difficult to obtain and culture in vitro. Defects developed in genetically modified animal models are notably different from human diseases at the molecular level. The advent of human induced pluripotent stem cells (hiPSCs) provides an unprecedented opportunity to further investigate the pathogenic mechanisms of inherited cardiomyopathies in vitro using patient-specific hiPSC-derived cardiomyocytes. In this review, we will make a summary of recent advances in in-vitro inherited cardiomyopathy modeling using hiPSCs.